Navigating the Challenges of Remote Work: Cross-Border Collaboration in a Virtual World - Malaila, Kampamba (Advances in Social Sciences Research Journal, 2025)
The global shift to remote work during the COVID-19 pandemic fundamentally transformed patterns of team interaction and organizational dynamics. While remote work offered flexibility and cost efficiency, it also introduced challenges that significantly affected teams operating across national and organizational boundaries. This study examined the key obstacles and potential benefits associated with remote collaboration among multinational virtual teams. Three primary challenges were identified: disparities in technological capabilities, differences in cultural preferences, and a reduced capacity to interpret nonverbal communication cues. Drawing on multiple peer-reviewed studies and qualitative interviews with multinational organizations, this research developed a comprehensive framework aimed at improving remote team effectiveness. The findings revealed that standardized technological platforms, cultural competence training, and transparent communication systems were critical for addressing these challenges. Implementing these strategies enhanced productivity, innovation, and employee satisfaction within virtual teams. Overall, the study contributed to bridging operational knowledge gaps for organizational managers navigating global workforce management through remote collaboration.